Influencing Factors of Cardiac Adaptation in Adolescent Athletes - Szabo, Dora; Nagy, Dora; Melczer, Csaba; Acs, Pongrac; Ratgeber, Laszlo; Szokodi, Istvan; Toth, Miklos; Cziraki, Attila; Eklics, Kata; Sarszegi, Zsolt (International Journal of Sports Medicine, 2021)
Endurance training-induced changes in left ventricular diastolic function and right ventricular parameters have been investigated extensively in adolescent athletes. Our aim was to examine the parameters for adolescent athletes (n=121, 15.1±1.6 years) compared to adult athletes and age-matched non-athletes. We explored the effects of influencing factors on the echocardiographic parameters. Significantly higher E/A (p<0.05) and e’ values (p<0.001) were detected in adolescent athletes compared to age-matched non-athletes’ and also adult athletes’ parameters. Significantly lower structural and functional right ventricular parameters (p<0.05) were detected in adult athletes. In adolescent athletes significantly higher right ventricular diameters, tricuspid S wave, right ventricular end-diastolic and end-systolic area values (p<0.05) were found compared to the matching parameters of non-athletes. We found significantly higher corrected tricuspid annular plane systolic excursion values (p<0.001) in athletes compared to the non-athletes. Based on multivariate analysis lean body mass, body surface area, age and cumulative training time were proved as strong predictive factors of both left ventricular diastolic and right ventricular parameters. Supernormal left ventricular diastolic function and significantly higher right ventricular parameters are indicative of cardiac adaptation. Well-defined cut-off values should be applied to discriminate pathological conditions in the relation of the influencing factors.
Keywords: left ventricular diastolic function; right ventricular parameters; echocardiography; sports cardiology